Cold Storage Effects on Oxidative Stress of Cv. Red Globe Table Grape Rachises [Efecto de Las Condiciones de Almacenamiento Refrigerado Sobre el Estrés Oxidativo en Raquis de Uva de Mesa, Cv. Red Globe] - Zuniga-Navarro, G; Kohler-Campos, H; Contreras-Arredondo, R (2012)
Table grape (Vitis vinifera L.) quality includes the condition of both the berries and the rachis. In the present report, physiological parameters of Red Globe rachises from fully elongated inflorescences (RFEI) and from mature clusters were studied after storage at 0 or 20 °C for different durations. To understand changes in rachis physiology as a result of changes in temperature conditions and storage time, the activities of superoxide dismutase (SOD), catalase (CAT) and ascorbate peroxidase (APX) were measured. In addition, hydrogen peroxide content, membrane lipoperoxidation (TBARS), total phenolic compounds and antioxidant capacity (FRAP) were assayed. TBARS was higher in mature rachises than in RFEI. This parameter remained constant throughout storage, indicating a change presumably associated with ontogeny or senescence processes. Short-term storage (0- 96 h) increased SOD, CAT and APX activities in RFEI, while in mature rachises, no changes were observed in enzyme activities or in hydrogen peroxide content. Longer cold storage (25 or 53 days at 0 °C) of mature rachises reduced CAT activity, but SOD and APX activities did not change under these conditions. At 0 h, the FRAP and total phenolic contents of mature rachises were three and 20 times higher than in immature rachises, respectively.